Rekomendasi Pemupukan Padi Sawah (Oryza sativa L.) Spesifik Lokasi di Kecamatan Malinau - Kabupaten Malinau - Hidayanto Hidayanto (Mulawarman University, 2019)
The area of paddy fields in Malinau Kota District is around 463 ha or 10.29 percent of the productive paddy in Malinau Regency which reaches 4,500 ha. The productivity of rice in the area is still low, which is around 3-4 ton ha-1, its caused by the use of fertilizers that are not yet suitable for plant growth requirement. Therefore, in order to improve rice productivity, it is necessary to do soil analysis to formulate spesific location fertilizer recommendations based on soil nutrient status. The assessment was carried out in Malinau District, Malinau Regency, on September-November 2017. The purpose of the asseement was to develop recommendations for fertilizing specific location lowland rice based on soil nutrient status. The assessment method is to take composite soil samples from several representative locations, then analyze in the laboratory, and the results of the analysis are used to formulate recommendations for specific location lowland rice fertilization. The results of soil analysis showed that soil pH was acid, organic C-content was low, N-tot was low, P was medium and K was medium. Recommendations of N fertilization with Urea as the basic fertilizer 50-100 kg ha-1 and subsequent N fertilization based on leaf color chart (LCC), P fertilization with SP-36 as much as 100 kg ha-1, and K fertilization with KCl as much as 50 kg ha-1.